"Not just a checkbox": A qualitative study of the resident scholarly experience. Issue 6 (20th December 2022) - Jordan, Jaime; Berger, Max; Curato, Mark; Ilgen, Jonathan S.; Hopson, Laura R.; Clarke, Samuel O.; Chipman, Anne K.; Janicki, Adam; Gottlieb, Michael
Abstract: Objectives: Scholarship is a requirement of residency training; however, the scholarly productivity of trainees is highly variable. The purpose of this study was to explore the perspectives of residents who have been highly productive in scholarship. Methods: We performed a qualitative study using a constructivist–interpretivist paradigm and conducted semistructured interviews at seven Accreditation Council for Graduate Medical Education–accredited emergency medicine residency programs in the United States. We included sites of diverse locations and training formats (PGY‐1 to ‐4 vs. PGY‐1 to ‐3). Program leadership identified residents with high levels of scholarly productivity at their institutions. We used purposive sampling to seek out residents with diversity in gender and PGY level. Two researchers independently performed a thematic analysis of interview transcripts. Discrepancies were resolved through in‐depth discussion and negotiated consensus. Results: We invited 14 residents and all consented to be interviewed. Residents felt scholarship enhanced their knowledge and skills, grew collaborative networks, and provided personal fulfillment and external rewards. Scholarship positively impacted their careers by focusing their professional interests and informing career decisions. Participants identified individual and institutional facilitators of success including personal prior knowledge and skills, project management skills, mindset, protected time, mentorship, and leadership support. Challenges to conducting scholarship included lack of time, expertise, and resources. Participants acknowledged that participating in scholarly activities was hard work and recommended that residents seek out quality mentorship, work on projects that they are passionate, start early, and be persistent in their efforts. Participants' advice to faculty supporting resident scholarship included recommendations to allow resident autonomy of projects, provide scholarly opportunities, and be responsive to trainee needs. Conclusions: Participants in this study highlighted benefits of participating in scholarly activity as well as challenges and strategies for success. These results can inform residencies seeking to enhance the scholarly experience of trainees.